Gestión integrada de la inocuidad en dietas especiales listas para el consumo - Maggi, M. L.; Maino, A.; Biasiol, G.; Maggi, L.; Lopez, A. (2024)
Fil: Maggi, M. L. Gobierno de la Provincia de Córdoba. CEPROCOR; Argentina.